Pendampingan Implementasi Kurikulum Merdeka Berbasis Moderasi Beragama di Kampung Segeram Kabupaten Natuna - Umar Natuna; Kartubi; Erine Agustia (STMIK Royal, 2025)
Abstract : This Community Service program was motivated by educational issues in Segeram Village, where apologetic and textual religious understandings have developed. Educational institutions in Segeram Village have not yet become a strong force in transforming the mindset of the younger generation, particularly in fostering a moderate understanding of religion to support the creation of a harmonious, dynamic, and diverse society. The community service team used the Participatory Action Research (PAR) method, which consists of three main stages: Focus Group Discussion (FGD), Training, and Implementation. Based on findings from the field activities, the following conclusions can be drawn: a) Educators are capable of formulating and implementing the Independent Curriculum based on Religious Moderation. b) There is active involvement of students, allowing the acquired knowledge to be applied in their daily lives. c) The community’s understanding of religious moderation has contributed to environmental harmony, encouraging people to better preserve and nurture human resources as vital sources of life that must be protected. Keywords: independent curriculum, religious moderation, PAR Abstrak : Pengabdian Kepada Masayarakat ini dilatarbelakangi oleh permasalahan pendidikan yang ada di kampung Segeram dimana berkembang paham keagamaan yang bersifat apologis dan tektual. Lembaga Pendidikan yang ada di Kampung Segeram tidak banyak menjadikan kekuatan perubahan pola pikir Masyarakat muda di Kampung Segeram, terutama dalam pemahaman agama yang moderat untuk menopang bangunan Masyarakat yang harmonis, dinamis dan beragam. Tim PKM menggunakan Metode Participary Action Reaserch (PAR) dimana memiliki 3 tahapan utama yaitu : FGD, Pelatihan dan Implementasi. Berdasarkan temuan pada kegiatan pengabdian di lapangan, maka dapat ditarik kesimpulan sebagai berikut: a)Tenaga pendidik sudah mampu merumuskan dan menerapkan materi Kurikulum Merdeka Berbasis Moderasi Beragama. b) Perlibatan aktif peserta didik sehingga pengetahuan yang diperoleh dapat diterapkan dalam kehidupan sehari-hari. c) Pemahaman masyarakat terkait moderasi beragama berdampak pada tercipta harmonisasi alam sehingga masyarakat lebih menjaga dan merawat sumber daya manusia sebagai sumber kehidupan yang harus dijaga. Kata kunci: kurikulum merdeka, moderasi beragama, PAR